Improving Students’ Reading Skill Through Preview, Ask Questions, Read, And Summarize (PARS) Strategy - putri, gita zania (Journal of English and Arabic Language Teaching, 2013)
The opening of reading interest must be compared with the effectiveness of the activity. A preview of the strategies used, Ask Questions, Read, and Summarize (PARS) that have been done can improve the memory and effectiveness of the reading itself. The methodology of this research is classroom action research. Data analysis in this study uses descriptive techniques whose data collection techniques are taken from the results of the pre-test and post-test. There are two groups involved in this study: the experimental group (EG) and the control group (CG). During implementation, the two groups experienced different treatments. The population selected in this study was 7th-grade learners from Junior High School 5 of South Tangerang. In selecting the sample, the researchers deliberately chose two groups (n = 60 students). To collect data, the researchers implemented a reading test. The purpose of this study is to find out which reading techniques are deemed appropriate for students and expect a significant compilation using the PARS strategy.